STUDI DESKRIPTIF SELF CONCEPT SISWA SMP NEGERI 1 BATUJAJAR - Fahdilla Noor Azizah; Ecep Supriatna; Reza Pahlevi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to describe the level of self-concept of students in SMP Negeri 1 Batujajar. The approach in this study is a quantitative approach with a descriptive method. Data collection in this study used an instrument in the form of the Tennessee Self Concept Scale (TSCS) of 100 statements adapted from previous research. The samples in this study were junior high school students in grades VII, VIII, and IX. The results showed that the self-concept of students at SMP Negeri 1 Batujajar was included in the medium category as many as 58 students with a percentage of 70% based on aspects of self-concept, namely identity, self-acceptance, behavior, physical, moral-ethical, personal, family, social, and social. self-criticism. Meanwhile, when viewed by gender, the moderate category is more dominant in female students as many as 54 students with a percentage of 65%. Based on age, the medium category which is more dominant in 14 year old students is 34 students with a percentage of 41%, and based on the category of the most dominant aspect, the medium category which is the most dominant in the family aspect is 56 students with a percentage of 76%. Keywords: : Self  concept, Junior High School Student